High-solid pretreatment of corn stover using urea for enzymatic saccharification. (July 2018) - Wang, Lili; Zhang, Ke; Xu, Youjie; Zhang, Meng; Wang, Donghai
Highlights: High-solid urea pretreatment of biomass realized gaseous ammonia treatment effect. Urea pretreatment of biomass at relative low temperature and pressure was feasible. Urea clearly enhanced the enzymatic saccharification effectiveness of corn stover. The optimal efficiency of enzymatic saccharification of glucose reached to 84.11%. Urea pretreatment apparently altered the morphological structure of corn stover. Abstract: The aim of this research was to study a high-solid pretreatment of corn stover using urea. Effects of solid loading (30–70%), temperature (60–80 °C), time (2–14 d), ratio of urea to corn stover (1:10–1:1), and ratio of soybean flour to corn stover (1:40–1:10) on enzymatic saccharification were investigated. Generally, the glucose and xylose yield increased as the reaction temperature, time, and ratio of urea to corn stover increased. Urea enhanced enzymatic saccharification at a relatively high-solid loading and low temperature. The results showed that 80 °C for 10 d with urea to corn stover ratio of 1:1 and 50% solid loading are optimum treatment condition to achieve high glucose recovery and enzymatic saccharification efficiency. Under optimum condition, 97.24% glucan and 61.63% xylan were preserved in the treated corn stover, and the maximum enzymatic saccharification efficiencies of 84.11% and 78.54% were achieved for glucose and xylose, respectively.